A Survey on the Awareness and Attitude of Physicians on Direct Oral Anticoagulants in Qatar - El-Bardissy, Ahmed (Clin Appl Thromb Hemost, 2018)
Direct oral anticoagulants (DOACs) are more commonly prescribed since their introduction. Reports on inappropriate prescribing have been observed which may indicate poor awareness on these agents. In this study, we aim to evaluate the extent of the physicians’ knowledge on DOACs and its possible impact on physicians’ confidence to prescribe these medications. A prospective cross-sectional survey was developed based on the literature review. Eligible participants were physicians and surgeons currently practicing at Hamad General Hospital in Qatar. The survey included questions on demographic and professional characteristics. It also evaluated the awareness and attitudes regarding safety, efficacy, and prescribing of DOACs. Over 6-month period, 175 practitioners responded to the survey. Overall awareness score was moderate (61% ± 18%). These scores were in alignment with participants’ self-satisfaction with knowledge on DOACs (66% were not satisfied) and participants’ confidence toward prescribing DOACs (48% were not confident). Age, degree of education, and years of experience had significant positive influence on awareness score. This survey indicates that practitioners have moderate awareness on DOACs. Future work should focus on reassessing practitioners’ knowledge after providing well-designed education campaigns